재난방송환경에서 유관중과 인터랙티브 스포츠 중계형식이 잠재 시청률과 방송사 인식에 미치는 효과 - 윤천석 (한국설비안전학회지, 2021)
The Corona pandemic is one of the major global disasters in modern times. Both governments and businesses have been forced to deal with it with maximum measures. The sport and broadcasters were not exceptions. For the first time in the Olympic history, the Summer Games were held spectator-free in 2021 in Tokyo. Prior to the COVID-19 crisis, it has been improbable that the Olympics could be held without spectators. This study looked into the viewer’s perceptions on sport broadcasters pertaining to the two different kinds of sports telecasts aired during the COVID-19 crisis. For this study, two experimental visual aids are made. The first one is a regular sport telecast with spectators of the pre-COVID era and the second is a spectator-free interactive telecast in which on-line viewers participated as guests. The three dependent variables were presented as ’broadcaster’s reputation’. ‘viewer’s attitudes toward a broadcast station’ and ‘intentions to watch’. The results showed that for all three dependent variables significant differences were found between a regular game telecast and an interactive one. It indicates that the interactive sport telecasts are favored by the viewers and thus enable sport networks to earn positive perceptions on organizational reputation, attitudinal loyalty and intenion to watch. It effectively denies the conventional wisdom of media professionals that spectators and their fan noise is an inevitable part of sport telecasts. This study shows that interactive telecasts will increase ratings and revenues for networks and should be the pivotal production format. Both sports and sport teams alike can benefit monetarily from the interactive telecast despite of little to no-stadium revenue. Both sports broadcasters and teams can benefit from these findings of interactive telecast.
Keywords: Telecasting in pandemic times; Perceptions on broadcast stations; Interactive sport telecasts